2021
DOI: 10.1016/j.mechrescom.2020.103615
|View full text |Cite
|
Sign up to set email alerts
|

Strain-path dependent hardening models with rigorously identical predictions under monotonic loading

Abstract: Accurate sheet metal simulation often requires advanced strain-path dependent material models, in order to predict the material response under complex loading conditions, including monotonic, reverse and orthogonal paths. More and more flexible models imply higher and higher costs in terms of parameter identification, computer implementation and simulation time, and robust comparison is often compromised by the inconsistent predictions of advanced models under monotonic loading. In this paper, a simple and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, in all BUT simulations, the friction effect is neglected because of the application of lubricant and the use of a free roller in the experiments. The von Mises plasticity function is used in all BUT simulation because Yang et al [40] confirmed the weak anisotropy of the investigated material, and given its negligible influence on the experimental springback results.…”
Section: Numerical Simulation Of But Testsmentioning
confidence: 99%
“…Moreover, in all BUT simulations, the friction effect is neglected because of the application of lubricant and the use of a free roller in the experiments. The von Mises plasticity function is used in all BUT simulation because Yang et al [40] confirmed the weak anisotropy of the investigated material, and given its negligible influence on the experimental springback results.…”
Section: Numerical Simulation Of But Testsmentioning
confidence: 99%
“…Thus, deriving the rate of 𝜎𝜎 * appears as a trivial extension of any arbitrary hardening model, while its analytical integration under an algebraic form may be difficult of impossible. The full development of the corresponding equations for the TH model can be found in [10].…”
Section: Experiments Modelmentioning
confidence: 99%